Finding Common Ground when Experts Disagree: Belief Dominance over Portfolios of Alternatives - Erin Baker; Valentina Bosetti; Ahti Salo (Fondazione Eni Enrico Mattei (FEEM), 2016)
We address the problem of choosing a portfolio of policies under “deep uncertainty.” We introduce the idea of belief dominance as a way to derive a set of non-dominated portfolios and robust individual alternatives. Our approach departs from the tradition of providing a single recommended portfolio; rather, it derives a group of good portfolios. The belief dominance concept allows us to synthesize multiple expert- or model- based beliefs by uncovering the range of alternatives that are intelligent responses to the range of beliefs. This goes beyond solutions that are optimal for any specific set of beliefs to uncover other defensible solutions that may not otherwise be revealed. We illustrate our approach using an important problem in the climate change and energy policy context: choosing among clean energy technology R&D portfolios. We demonstrate how the belief dominance concept can reveal portfolios and alternatives that would otherwise remain uncovered.
Keywords: D8; D78; D81; 330; Deep Uncertainty; Decision Making under Uncertainty; Robust; Dominance